The Role of Rice Hull Liquid Smoke in the Traumatic Ulcer Healing - Arundina, Ira; Diyatri, Indeswati; Kusumaningsih, Tuti; Surboyo, Meircurius Dwi Condro; Monica, Elita; Afanda, Novitasari Mira (European Journal of Dentistry, 2020)
Objective The aim of this study was to prove the role of rice hull liquid smoke (RH-LS) on lymphocytes, macrophages, fibroblasts, interleukin 6 (IL-6), and transforming growth factor β (TGF-β) expression during traumatic ulcer healing.Materials and Methods The RH-LS was obtained from the pyrolysis process. Traumatic ulcers were made 10 mm along the labial fornix incisive inferior of Wistar rat using a round stainless-steel blade. In control group, traumatic ulcers were treated using sterile water, and meanwhile in experimental group were treated using RH-LS once a day for 3, 5, and 7 days. After treatment, animal was terminated and their labial fornix incisive inferior tissues were biopsy and stained using hematoxylin and eosin staining to determine lymphocytes, macrophages, and fibroblasts. The IL-6 and TGF-β expressions were analyzed used immunohistochemistry staining.Result The lymphocytes, macrophages, and fibroblasts were higher in the RH-LS group for 3-, 5-, and 7-day treatment (p < 0.05). The IL-6 expression was higher only in the 5-day treatment, and the TGF-β expression was higher in the 3- and 7-day treatment.Conclusion The RH-LS able to accelerated the traumatic ulcer healing by increasing the number of lymphocytes, macrophages, fibroblasts, IL-6, and TGF-β expression.
Keywords: traumatic ulcer; fibroblast; macrophage; lymphocyte; rice hull; liquid smoke; IL-6 and TGF-β